2007
DOI: 10.1111/j.1600-6143.2007.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Recurrence and Death Following Living and Deceased Donor Liver Transplantation

Abstract: We examined mortality and recurrence of hepatocellular carcinoma (HCC) among 106 transplant candidates with cirrhosis and HCC who had a potential living donor evaluated between January 1998 and February 2003 at the nine centers participating in the Adult-toAdult Living Donor Liver Transplantation Cohort Study (A2ALL). Cox regression models were fitted to compare time from donor evaluation and time from transplant to death or HCC recurrence between 58 living donor liver transplant (LDLT) and 34 deceased donor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
195
6
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(213 citation statements)
references
References 22 publications
8
195
6
4
Order By: Relevance
“…Although LDLT was used as an alternative treatment for HCC in times of shortage of donor livers, high HCC recurrence rates associated with LDLT have been reported, which were attributed to the fact that SFSGs are relatively more frequently used in LDLT than in DDLT. (7)(8)(9) However, Hwang et al and Gondolesi et al reported no difference in oncologic outcomes between LDLT and DDLT. (10)(11)(12) As can be seen, controversies exist regarding the association between SFSG and HCC recurrence, and several important points have been overlooked in the previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although LDLT was used as an alternative treatment for HCC in times of shortage of donor livers, high HCC recurrence rates associated with LDLT have been reported, which were attributed to the fact that SFSGs are relatively more frequently used in LDLT than in DDLT. (7)(8)(9) However, Hwang et al and Gondolesi et al reported no difference in oncologic outcomes between LDLT and DDLT. (10)(11)(12) As can be seen, controversies exist regarding the association between SFSG and HCC recurrence, and several important points have been overlooked in the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…HBV infection was found in 89.3% (n 5 293) of recipients. The median Child-Pugh score was 6 (interquartile range [IQR], [4][5][6][7][8], and the median MELD score was 11 (IQR, 9-16). With regard to T stage, T2 was the most common, observed in 58.2% (n 5 191) of the patients, followed by T1 in 23.5% (n 5 77) of the patients.…”
Section: Baseline Characteristics Of the Propensity-matched Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six published articles comparing LDLT and DDLT for HCC with CEBM level 1b evidence were identified, [1][2][3][4][5][6] and they are listed in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some centers have been reluctant to offer LDLT for HCC because of concerns about higher rates of cancer recurrence and inferior patient survival after LDLT versus deceased donor liver transplantation (DDLT). [1][2][3][4][5][6] Theoretical reasons for concerns about the potential for higher rates of HCC recurrence after LDLT include the following: (1) the stimulation of residual cancer cells by growth factors in the regenerating liver 7 ; (2) the relatively brief waiting time for LDLT, which may allow transplantation for patients whose aggressive or rapidly progressive HCC tumors might progress with a longer waiting time and exclude them from transplantation 8 ; and (3) more limited oncological clearance with the inferior vena cava-sparing technique used for LDLT. Another explanation for the reports of higher recurrence rates after LDLT is the presence of programmatic biases that lead these centers to unknowingly offer LDLT to patients with a higher risk of HCC recurrence.…”
mentioning
confidence: 99%